The finer points of sausage dogs [large type] - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- Professor Dr. von Igelfeld entertainment novel., 2006)
Invited to lecture in America, von Igelfeld envisions a visit to California or New York. Instead, he finds himself at the University of Arkansas. Still, in von Igelfeld's view, one American state is very like the other. An expert philolgist, von Igelfeld prepares to deliver a talk on verbs, until he makes a grim discovery--he has been mistaken for a German master of veterinary science who has recently passed away.